The Development of Tahfizd Institution and PAI in Indonesia - Nur, Muhammad; Iswantir, Iswantir (The Future of Education Journal, 2023)
Tahfidz institutions in Indonesia continue to develop as a sign of the rise of enthusiasm and enthusiasm for Islam in the midst of a humanitarian crisis. changes try to contextualize the curriculum with the times, but the exchange of curricula which alternates and is tentative in nature creates mass confusion for education practitioners as bearers of the mandate of educational and scientific transformation for students. The research applied literature review, in which several academic works relevant to the topic are critically selected. Literature is collected from many sources, including articles from leading academic journals, books and more. Then, the selected literature is critically analyzed and evaluated to find the required information. The study shows that Islamic Religious Education, all of this shows the high enthusiasm of the Indonesian Muslim community to memorize the Al-Qur'an and make their children memorize the Al-Qur'an as well as efforts to improve the quality of Islamic Religious education from time to time. The development of PAI in Indonesia is a long journey taken by the Islamic community with all its dynamics, and is full of curriculum changes that alternate from time to time, so that PAI in Indonesia is a curriculum that is dynamic and rich in changes.